Integration of Philanthropy and Capital Market: Legal Analysis and Economic Impact of Cash Waqf Linked Sukuk in Indonesia - Ibrohim, Muhammad; Athiyah, Ummu (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Purpose: This study aims to analyze the integration of cash waqf with Islamic capital market instruments through the Cash Waqf Linked Sukuk (CWLS) scheme in Indonesia, focusing on aspects of sharia legitimacy, management mechanisms, and its impact on the community's economy. Methodology: This research uses a qualitative approach with content analysis and case study methods. Data was collected through a literature review of fatwas, regulations, implementation reports, and academic publications related to CWLS. Analysis was conducted descriptively and critically to evaluate the contract construction, implementation, and socio-economic impact. Results: CWLS successfully connects the Islamic philanthropic sector with state financing through sukuk, with the legal foundation of DSN-MUI Fatwa No. 131/2019. This instrument upholds the principle of the perpetuity of waqf assets through a state guarantee, while also generating social benefits channeled to the health, education, and MSME sectors. Applications/Originality/Value: This study provides an academic contribution to understanding the transformation of waqf from a conventional to a contemporary model, as well as offering policy recommendations to enhance the effectiveness and accountability of productive waqf management in Indonesia.